2011
DOI: 10.1016/j.ceramint.2011.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of highly textured porous Ni–YSZ and Co–YSZ cermets produced from directionally solidified eutectics

Abstract: It is well known that several ceramic materials develop an usual; and sometimes unique; combination of properties as a result of mixing different phases with similar expansion coefficients. Sometimes they are elastically stiff, have relatively low thermal expansion coefficients, good thermal and electrical conductivities, and are resistant to chemical attack.As this paper will show, their mechanical properties are also enhanced. Nanoindentation technique is used to measure the mechanical properties for each ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This value is slightly higher than the value previously obtained from the raw indentation data. For comparison, the elastic modulus of a dense yttria stabilized zirconia is around 200 GPa and the hardness ranging between 10 and 15 GPa [54][55][56][57][58]. For example, Roa et al [55] found the highest value for the hardness by nanoindentation limiting the indentation depth to 100 nm.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This value is slightly higher than the value previously obtained from the raw indentation data. For comparison, the elastic modulus of a dense yttria stabilized zirconia is around 200 GPa and the hardness ranging between 10 and 15 GPa [54][55][56][57][58]. For example, Roa et al [55] found the highest value for the hardness by nanoindentation limiting the indentation depth to 100 nm.…”
Section: Resultsmentioning
confidence: 96%
“…For comparison, the elastic modulus of a dense yttria stabilized zirconia is around 200 GPa and the hardness ranging between 10 and 15 GPa [54][55][56][57][58]. For example, Roa et al [55] found the highest value for the hardness by nanoindentation limiting the indentation depth to 100 nm. Jang and Matsubara [56] and Lugscheider et al [58] have found similar values on YSZ coatings obtained by EB-PVD technique.…”
Section: Resultsmentioning
confidence: 96%
“…Employing zirconia as an anticorrosive would be an alternative for improving metal-alkyd coating adhesion. It is known that ZrO 2 is characterized by its excellent properties of resistance to corrosion and that it can be synthesized by means of various methods [17][18][19][20]. Zirconia deposited as a thin lm on various types of steel has been shown to increase the corrosion resistance of the substrate [21][22][23], and as a buffer layer, it increases the corrosion resistance of epoxy paints [11].…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerability of SOFCs to mechanical failure is a well‐known issue. However, much of the research into this phenomenon has focused on yttrium stabilized zirconia (YSZ) based devices . This material has been the standard for the field and has desirable mechanical properties but requires high temperatures to function well.…”
Section: Introductionmentioning
confidence: 99%
“…However, much of the research into this phenomenon has focused on yttrium stabilized zirconia (YSZ) based devices. [2][3][4] This material has been the standard for the field and has desirable mechanical properties but requires high temperatures to function well. As efforts are made to lower SOFC operating temperatures, a shift to ceria-based electrolytes has occurred.…”
Section: Introductionmentioning
confidence: 99%